Jejak Pengalaman Wirausahawan: Menguak Dinamika Keputusan Pemasaran pada Startup Business - Sanny Tanner Sapulete; Meike Elsa Toisuta (Journal of Innovative and Creativity, 2025)
This study aims to examine the influence of knowledge and work experience on entrepreneurial decision-making. The research employed multiple linear regression analysis. The results indicate that knowledge and work experience simultaneously have a significant effect on entrepreneurial decision-making (p < 0.05). However, multicollinearity testing revealed a tolerance value of 0.000 for the knowledge variable, indicating perfect multicollinearity with the work experience variable. As a result, the knowledge variable was excluded from the model due to its lack of independent contribution to the dependent variable. These findings suggest that work experience exerts a more dominant influence in entrepreneurial decision-making, providing practical skills and contextual understanding that surpass the impact of theoretical knowledge alone. Thus, work experience plays a more substantial role in enabling individuals to make effective entrepreneurial decisions.